Success factors at university from students’ perspective - Saud, Wafa Ismail (Technium Social Sciences Journal, 2021)
The aim of the present qualitative study was to explore the factors that support or hinder students from achieving their goals while they are at university. The participants were 84 undergraduates majoring in English at King Khalid University. Constructed interviews with students were used for eliciting information. The data were analysed stating and combining the similar factors and calculating their frequencies and percentages. The findings indicated that external support from family, friends and society was the main factor for students’ success followed by determination and persistence, ambition, hard work and patience. On the other hand, discouragement was the main factor that hinders students’ success, followed by irresponsibility, carelessness and laziness, then by poor time management and finally, failure and frustration. Implications for English language professionals and areas for further research were suggested.